1996
DOI: 10.1136/vr.138.24.586
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of lameness in dairy cattle: description and analysis of foot lesions

Abstract: Information from 37 dairy farms, in four regions of England and Wales provided data on 8991 lesions and the preventive trimming of 4837 cows' feet. Of the total of 13,828 forms returned, veterinary surgeons treated 32 per cent and farmers or stockmen 46 per cent. Of the 8645 lesions associated with episodes of lameness, lesions in the hindlimbs accounted for 92 per cent, of which 65 per cent were in the outer claw, 20 per cent in the skin and 14 per cent in the inner claw. Sole ulcers (40 per cent) and white l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
152
2
23

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(188 citation statements)
references
References 6 publications
11
152
2
23
Order By: Relevance
“…Estas condições contribuem para desgaste dos cascos e consequentemente a ocorrência de lesões podais, como descreveram Albuquerque et al (2009). A maioria das afecções podais, mais exatamente 96%, acometiam os membros pélvicos nas vacas avaliadas, assim como encontrado por Murray et al (1996), Molina et al (1999), Silva et al (2001), Machado et al (2008) e Cunha (2010. O maior envolvimento dos membros pélvicos nas afeções podais pode ser devido à alterações conformacionais, originadas principalmente pelo volume e posicionamento do úbere, causando maior pressão sobre os dígitos laterais dos membros pélvicos.…”
Section: Discussionunclassified
“…Estas condições contribuem para desgaste dos cascos e consequentemente a ocorrência de lesões podais, como descreveram Albuquerque et al (2009). A maioria das afecções podais, mais exatamente 96%, acometiam os membros pélvicos nas vacas avaliadas, assim como encontrado por Murray et al (1996), Molina et al (1999), Silva et al (2001), Machado et al (2008) e Cunha (2010. O maior envolvimento dos membros pélvicos nas afeções podais pode ser devido à alterações conformacionais, originadas principalmente pelo volume e posicionamento do úbere, causando maior pressão sobre os dígitos laterais dos membros pélvicos.…”
Section: Discussionunclassified
“…In Denmark, lameness prevalence increased after periods of high rainfall [13] but Whitaker et al (2004) found no such relationship in UK dairy cattle [14]. In an epidemiological-study of dairy cow lameness involving 37 farms, the incidence of specific lesions associated with lameness were significantly higher in the winter time than in summer, particularly claw diseases such as heel horn erosion [15]. In New Zealand, Tranter and Morris (1991) showed that a peak incidence of lameness occurred during the winter and the late spring, its onset being associated with wet weather conditions [16]; a similar trend was reported by Jubb and Malmo (1991) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Segundo este autor a prevalência é importante para intervir e tratar o animal afetado naquele momento, enquanto que a incidência está relacionada na evolução, prevenção e na reincidência dos casos. A principal manifestação clínica das podopatias em ruminantes é representada pelas claudicações, sendo que 90% das enfermidades do aparelho locomotor dos bovinos se localizam na região distal dos membros, afetando os dígitos e cascos (Murray et al, 1996). De todas as lesões podais 66,67% estão localizadas nos membros pélvicos (Molina et al, 1999).…”
Section: éTica No Uso De Animais Acometidos Por Podopatias Na Exploraunclassified